Coevolution of the male and female reproductive tracts in an old endemic murine rodent of Australia. (18th October 2012) - Breed, W. G.; Leigh, C. M.; Speight, N.
Abstract The male reproductive tract of most Australian hopping mice in the genus Notomys has a suite of highly derived features that differ markedly from those of other Australian rodents. These include, among others, extremely small testes, a reduced complement of accessory sex glands and a spiny penis. Here we ask the question – what are the coevolved features of the female reproductive tract? To answer this question, we used histology and resin casts to compare the reproductive tract of the Australian plains mouse (Pseudomys australis) with that of the Spinifex hopping mouse (Notomys alexis). In P. australis, the cervix is highly fibrous and has two small canals whereas the vagina has prominent fornices, a large lumen and a folded epithelial lining. By contrast, in N. alexis the cervix is not prominent and is far more cellular. It has a very small, single lumen with the boundary between it and the vagina not being readily evident. The vagina has minute fornices and is surrounded by a comparatively thick muscle coat. Shortly after ejaculation, N. alexis had many uterine sperm that associated with coagulated material but, unlike in P.australis, no large vaginal plug occurs after ejaculation. These observations support the conclusion that N. alexis has a highly derived distal region of the female reproductive tract which has coevolved with that of the male. It appears to facilitate rapid sperm transport postcoitum without the need for a large copulatory plug.